Trash is good business:: Adam Minter and his Junkyard Planet - Almeida, Valéria Gentil (Sustainability in Debate, 2015)
Adam Minter. Junkyard Planet: Travels in the Billion-Dollar Trash Trade. London: Bloomsbury Press, 2013. Includes photographs, index, maps. ISBN 9781608197910